Subsurface Flow and Surface Water Interactions Quantification in Gunung Kidul Karst Area Using Hydro- Chemical and Stable Isotopes Data Variations - Sidauruk, Paston; Pujiindiyati, E. Ristin; Satrio, Satrio (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2016)
Subsurface flow is one of the available water sources in the Karsts area such as in GunungKidul. The study of the pattern of the variations of stable isotopes content as a function oftime and its interaction with other water sources such as rain waters, groundwater, riverwater will be a very good tool to assess the potential of the subsurface flow as a water source.For this purpose, the variations of stable isotopes content of subsurface flow around GunungKidul Karsts area and its interactions with other local water sources have been studied for thelast two years. From the comparison of stable isotopes variations pattern of the subsurfaceflow with monthly rain water, the interaction of the subsurface flow with other water sourcesin the area has been quantified. Based on hydro-chemical data, it was found that the rechargearea of subsurface flow were relatively further than other samples and it was also found thatSeropan and Bribin subsurface flow systems originate from different geologic structures.Based on stable isotopes relative contents, it was found Ngobaran and Baron Caves have beenmixed with domestic sewerage water or other surface water.